Fascism, nazism and the Holocaust : challenging histories - Stone, Dan 1971- (Routledge studies in fascism and the far right, 2021)
Introduction: Challenging histories -- 'The ultimate cross-cultural fertilizer' : the irony of the 'transnational local' in Anglo-German rural revivalism -- Aurel Kolnai's The war against the West and British attempts to understand Nazism before the war -- Race science, race mysticism, and the racial state -- Nazi race ideologues -- Ideologies of race : the construction and suppression of otherness in Nazi Germany -- Structure and fantasy : Holocaust perpetrators and genocide studies -- Christianstadt : slave labour and the Holocaust -- Belsen and the British -- The Iron Guard in Nazi captivity : evidence from the International Tracing Service -- Romania and the Jews in the BBC Monitoring Service reports, 1938-1948 -- Concentration camps : a global history -- The course of history : Arno J. Mayer, Gerhard L. Weinberg and David Cesarani on the Holocaust and World War II -- The return of fascism in Europe? Reflections on history and the current situation.